(untitled) (Global Journal of Management and Business Research, 2019)
Total Quality Management (TQM), adopted by organizations to improve performance, has often been reported to have failed. This paper reviews people-related TQM practices, organizational culture, organizational justice, and employee work attitudes (job satisfaction, turnover intention, and job involvement) to gain further insights into implementing TQM to yield anticipated quality performance. Employee work-related attitudes are posited as mediators in the relationship between people- related TQM practices and quality performance. In a unique contribution, the paper conceptualizes the synergistic effect of people-related TQM practices and other people-related factors (organizational culture and organizational justice) as predictors of enhanced employee work-related attitudes and quality performance.